Pengaruh Capital Adequacy Ratio, Non-Performing Financing Dan Biaya Operasional Pendapatan Operasional Terhadap Kinerja Keuangan Perusahaan - Habib Musthafa; Wastam Wahyu Hidayat; Endah Prawesti Ningrum (Akuntansi, 2023)
The purpose of this study was to find out and analyze the effect of Capital Adequacy Ratio, Non-Performing Financing and Operational Income Operating Costs on Financial Performance in banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The samples used in this study were 22 companies. The sample was selected using purposive sampling method. The analytical method used in this study is descriptive statistics, t test, F test and the coefficient of determination using the adjusted R square. Test data using SPSS version 25 by using multiple regression tests and hypothesis testing. Partial testing with the t test shows that the Capital Adequacy Ratio (CAR) has a negative effect on financial performance, Non-Performing Financing (NPF) has no effect on financial performance, Operating Costs Operating Income (BOPO) has a negative effect on financial performance. The results of simultaneous testing with the F test are that the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) and Operational Income Operating Costs (BOPO) have an effect on financial performance.